Modeling of Solid ( Nd:YAG) Laser Operating with a Saturable Absorber Q-switch (Latakia University Journal -Basic Sciences Series, 2021)
The simulation of solid laser system operating with a saturable absorber Q-switch Cr+4:YAG was obtained as a numerical solution for this model. The solution was implemented in two different numerical methods and comparing between them. The laser output shape and characteristics were calculated and compared with experimental results